Strategi Pembelajaran Siswa Autis Pada Masa Pandemi di SLB Dharma Bakti Patianrowo - Rimalia Rimalia Dwi Krisnawati (Balitbangda Provinsi Jambi, 2022)
Abstract The learning strategy/method is the most important part in the implementation of teaching and learning activities. Teaching and learning activities for children with special needs certainly have special handling. For students with autism or autistic students, teaching and learning activities emphasize visual learning methods. Learning strategies can be determined based on various aspects such as methods, media, implementation leaarning and teaching processes, learning materials, and most importantly good cooperation between schools, teachers and parents is needed to create effective online teaching and learning activities for autistic students. During the COVID-19 pandemic, the learning strategy followed the policy set by the government, namely distance learning with an online system. This study uses a qualitative descriptive research method with data collection methods through interview techniques with resource persons, namely the principal and teachers of class XII autistic students and observations made by observing the implementation of teaching and learning activities. This study aims to identify challenges and obstacles in the implementation of online teaching and learning activities during the pandemic for autistic students and to describe strategies/methods for implementing learning for autistic students during the pandemic at SLB Dharma Bakti Patianrowo. Visual learning strategies/methods are maintained as well as adapting the character of autistic students and the role of parents is very much needed in online teaching and learning activities during the pandemic. This is due to the conditions and characteristics of autistic students who have not been able to carry out their own teaching and learning activities without assistance.